The Effect of Multidimensional Factors on Organizational Adoption of Enterprise Architecture: The Moderating Role of Organization Type - Ahmad N.A.; Drus S.M.; Kasim H. (IOP Publishing Ltd, 2023)
Surveys; Enterprise Architecture; ICT infrastructures; Malaysian public sectors; Organizational adoptions; Public sector organization; Technology adoption models; Technology-organization-environment frameworks; Top management support; Decision making